On-line monitoring of particulate processes using digital holography - Taslima Khanam (2011)
Digital holography is an effective three’ dimensional imaging technique, with the potential to be used for particle size measurements. A digital hologram can provide reconstructions of volume samples focused at different depths, overcoming the focusing problems encountered by other imaging based techniques. This work explores the potential of digital holography as a tool for online measurement of size and shape of micro particles. The first part of the thesis deals with the development of a technique to obtain 2D information of particles. The system was validated for both spherical and non-spherical (needle shaped) particles. The results from holography are shown to be fully consistent with those from independent techniques such as scanning electron microscopy. While 2D information is sufficient to describe spherical particles, it does not provide accurate information concerning nonspherica1, especially needle- shaped particles. An accurate measurement of the lengths is possible only if the orientation can be unambiguously measured, In order to address this problem, two novel techniques have been developed which simultaneously measure the location, orientation and length of a population of fibers. These have demonstrated by careful validation using single fibers and applied to a fiber population. Finally the technique has been applied to monitor the crystallization of transparent crystals of oxalic acid and measured their growth rate. The results obtained from this work adequately demonstrate the potential of digital holography as a reliable tool for the online monitoring of particulate processes.